Successful radical induced cationic frontal polymerization of epoxy-based monomers by C–C labile compounds. Issue 47 (8th October 2015) - Bomze, D.; Knaack, P.; Liska, R.
Abstract : Successful radical induced cationic frontal polymerization of epoxy-based monomers by C–C labile compounds. Abstract : Thermal bulk curing of epoxy resins is a non-energy efficient method. On the other hand classical photocuring techniques for epoxy resins are limited to quite thin layers, due to the limited penetration depth of UV-light. We show that Radical Induced Cationic Frontal Polymerization (RICFP ) is a promising technique for the energy efficient bulk curing of epoxy resins. The combination of a C–C labile compound (1, 1, 2, 2-tetraphenylethanediol) as a thermal radical initiator with diaryliodonium salts results upon local thermal- or photoinitiation in a self-sustaining front moving along the formulation and curing cationically curable resins completely. This allows the curing of monomer formulations in places that are not easily accessible or on objects that cannot be thermally cured because of their thermal instability or size. In this paper we report about first basic investigations onRICFP of several epoxy resins with C–C-labile compounds and compare them to common thermal radical initiators.